Comparison of shear bond strength of three different adhesives used as temporary bite raiser in daily orthodontic practice - Kılınç, Delal Dara; Sayar, Gülşılay (Elsevier Masson Sas Editeur, 2018)
Objective: The aim of this study was to evaluate the shear bond strength of three different adhesives (Transbond XT, Light Cure Adhesive, 3M Unitek; Transbond Plus, Light Cure Band Adhesive, 3M Unitek; Transbond Supreme LV, Low Viscosity Light Cure Adhesive, 3M Unitek), which were applied to the etched enamel of occlusal faces of mandibular molar teeth to gain bite opening. The null hypothesis was that there is no statistically significant difference between shear bond strength of these three adhesives. Materials and methods: Forty-eight human molar teeth were equally divided into three groups (n = 16). Teeth were embedded in self-curing acrylic resin and were polished and etched. Adhesives were applied on the teeth and all adhesives were light cured for 20 seconds. Universal Testing Machine was used for shear bond strength tests with a crosshead blade loaded at a crosshead speed of 1 mm/min. Evaluating the type of failure was done by using Adhesive Remnant Index (ARI) was used to evaluate the remaining adhesive on the tooth. Results: One-way analysis of variance (ANOVA) was used to determine the significant differences between the three different orthodontic adhesives. There was no significant difference (P = 0.774) between the groups according to ANOVA test. According to Kruskal-Wallis test there was no statistically significant differences in ARI scores among groups (P <0.01). Conclusion: The null hypothesis was accepted. There was no statistically significant difference among their bond strength values. All of three materials can be used as temporary bite openers.
WOS: 000442735000003
PubMed ID: 30006080
Keywords: Bite Raiser; Orthodontic Adhesives; Bond Strength; Bonding; Orthodontics